EXPLORING THE ADOPTION OF ARTIFICIAL INTELLIGENCE IN INSTITUTIONS OF HIGHER LEARNING - Shahrizal Nazri; Mohamed Azlan Ashaari; Hazrieffendy Bakri, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
In every sector of the economy, artificial intelligence (AI) is becoming more feasible, and higher education service is no exception. At an unparalleled pace, both within and outside the classroom, AI opens the possibility for institutions of higher learning (IHLs) to become scalable. This paper proposed a research framework for AI adoption of in IHLs. The research aims to examine the determinants that significantly affected AI adoption among IHLs. This study presents an interpretation of the Technology-Organisation-Environment (TOE) theory for the adoption of AI. The research framework derived from the TOE theory, where the context of technological, organisational, and environmental are vital for IT adoption. It discussed the development of hypotheses that consisted the determinants for the adoption of AI from the context of technological (relative advantage and compatibility), organisational (resources availability, top management support and organisation size) and environmental (government regulation and competitive pressure).